1996
DOI: 10.1016/0014-5793(96)00046-4
|View full text |Cite|
|
Sign up to set email alerts
|

Antioxidants differentially affect nuclear factor κB‐mediated nitric oxide synthase expression in vascular smooth muscle cells

Abstract: Increased 'oxidative stress' resulting in the activation of nuclear factor •B (NF-KB) is thought to play a crucial role in the cytokine-mediated expression of the inducible isoform of nitric oxide synthase (iNOS) in different cell types. Therefore, the effects of four different antioxidants, carbocromen, chrysin, 3,4-dichloroisocoumarin (DCI) and N-acetylserotonin (NAS), on iNOS expression were investigated in vascular smooth muscle cells (VSMC). All antioxidants strongly reduced the phorbol ester-stimulated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
2

Year Published

1997
1997
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 27 publications
1
19
0
2
Order By: Relevance
“…The proinflammatory cytokines (TNF-␣, IL-1␤, and IFN-␥) and LPS utilized in this study have been previously shown to induce expression of iNOS in vascular smooth muscle cells (1)(2)(3)(4)(5), and the increased production of nitric oxide that accompanies the induction of iNOS is thought to contribute in the pathophysiology of sepsis and other inflammatory disorders (1)(2)(3)(4)(5). The expression of iNOS was significantly increased after inhibition of nitric oxide production (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The proinflammatory cytokines (TNF-␣, IL-1␤, and IFN-␥) and LPS utilized in this study have been previously shown to induce expression of iNOS in vascular smooth muscle cells (1)(2)(3)(4)(5), and the increased production of nitric oxide that accompanies the induction of iNOS is thought to contribute in the pathophysiology of sepsis and other inflammatory disorders (1)(2)(3)(4)(5). The expression of iNOS was significantly increased after inhibition of nitric oxide production (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…3). NF-B is one of the transcriptional factors that mediates transcription of iNOS in rat smooth muscle cells (2)(3)(4), and numerous studies have implicated reactive oxygen species in the regulation of NF-B activity under inflammatory conditions (11)(12)(13)(14)(15). The data in this cell model system indicate that upon stimulation with cytokines and LPS, endogenous H 2 O 2 prevents the activation of this transcription factor, consistent with observations in alve- Cells stably transfected with catalase demonstrated cytokine-mediated intracellular protein nitration comparable to that of the vector-transfected control cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In rat thoracic VSM cells, pharmacological antioxidants have been shown to modulate NF-κB activation [64,70,88]. We as well as others have shown that NF-κB activity is potentiated by increased protein levels of catalase, although in this case the mechanisms of action have not been delineated [42,60].…”
Section: Regulation Of Inos Activity and Expressionmentioning
confidence: 81%